Hodgkin and non-Hodgkin lymphomas in pediatric-age patients of Northeast Mexico: 18-year outcomes and survival rates at an academic center - José C. Jaime-Pérez; Ana L. Beltrán-López; Valentina Jiménez-Antolínez; Renata Barragán-Longoria; Julia E. Colunga-Pedraza; Óscar González-Llano; David Gómez-Almaguer (Boletín Médico del Hospital Infantil de México)
Background: Hodgkin lymphoma (HL) and non-HL (NHL) are the third and fourth most common malignancies during childhood, with limited information available from Latin America. Method: We retrospectively studied patients with HL and NHL from a single academic center in Northeast Mexico between 2002 and 2020. Data included treatment regimens, staging, and survival outcomes. Survival was determined by Kaplan–Meier analysis, and features of lymphomas were compared using the X2 test. Results: The study included 75 patients, 36 (48%) with HL and 39 (52%) with NHL. Males predominated (70%); the median age was 9 years. Stages III and IV were detected in 59% and median follow-up reached 50 months. Relapse occurred in 16 (21%) patients, 9 (12%) in the HL group and 7 (9%) in the NHL group. Thirteen (17.3%) patients underwent transplantation, 12 (85%) in the HL group; 11 are alive. Most deaths, 10/11 (91%), occurred in NHL patients. Five-year overall survival rates were 96% (95% confidence interval [CI] 95.6-97) for HL and 75% (95% CI 74.9-76.3) for NHL (p = 0.004). Five-year disease-free survival was 70% for HL (95% CI 69-72.5) and 69% (95% CI 67.7-71) for NHL (p = 0.672). Conclusion: Pediatric-age HL and NHL had similar frequency in the study population; most patients presented with advanced disease at diagnosis. A high success rate was documented for HL, while NHL outcomes were suboptimal.